Semantic Web technologies for retrieval of data and agricultural information: a study of International Information Systemm of the Agricultural Science and Technology (AGRIS) - Moreira, Fabio Mosso [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP]; Santarem Segundo, Jose Eduardo; Vidotti, Silvana Aparecida Borsetti Gregorio (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2015)
The agricultural information is distributed in different actors and institutions. A lot of this information is available in digital format and can be accessed with web technologies. However, the diversity in conceptual coverage of the topics in the area of lexical heterogeneity of terms used for research are barriers in data retrieval of agricultural information. The Semantic Web technologies can contribute in reducing those barriers by standardizing the semantic representation of information resources available on the web. Thus, this paper aims to describe the semantic technologies used in the Information System of the International Agricultural Science and Technology - AGRIS, and point out their role in retrieval of data and agricultural information. Through a literature review and an exploratory analysis on the AGRIS web portal we describe how technologies can be used by the system and its main contributions.
Keywords: Agricultural information; Semantic Web; Retrieval of data and information